Der lange Schatten der Finanzkrise - Brumm, Kai; Hörisch, Felix (Zeitschrift für vergleichende Politikwissenschaft, 2018)
How have OECD democracies reacted to the emerging sovereign debt crisis? Why did some countries pass extensive consolidation programs while others maintain an expansionary fiscal policy? Finally, what explains the cross-sectional differences in the composition of deficit-reduction packages? Guided by established theories of comparative policy research and political economy, this contribution presents the results of two Qualitative Comparative Analyses (QCA) to address the aforementioned questions. Regarding the size of consolidation packages, the article underscores hypotheses derived from the varieties of capitalism literature: namely, that coordinated market economies (CMEs) only implement austerity measures when subjected to serious fiscal pressure, while liberal market economies (LMEs) see leftist parties urged to enact far-reaching budget reforms, provided that less fragmented cabinets facilitate the enforcement of such policies. Distinct party effects that occur independently from other factors, however, cannot be detected. Rather, even under market-friendly governments, an acute problem pressure is required in order to pass ambitious deficit-reduction plans. Meanwhile, in terms of the composition of consolidation packages, the findings of the present study contradict the expectations of classic partisan theory. In CMEs, particularly leftist and Christian democratic majorities have concentrated on reducing government spending. Liberal cabinets in CMEs, for their part, have implemented tax hikes to sustain high public expenditure levels. Finally, weak trade unions have been found to favor relatively large reductions in government expenditure, whether the state in question is ruled by especially market-friendly, centrist, or leftist parties.